Korelasi antara Kemampuan Membaca Al-Qur’an dengan Keterampilan Menulis Huruf Arab pada Mata Pelajaran Al-Qur’an Hadits di Madrasah Ibtidaiyah Quraniah 8 Palembang - Aquami Aquami (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2017)
This research aims to determine the correlation between the ability to read Al-Qur'an among students with Arabic writing skills on the subject of Al-Qur'an Hadith in MI Quraniah 8 Palembang. This research uses purposive sample that is sampling taken because there is a certain reason, taken from the VA class in MI Quraniah 8 Palembang, amounting to 26 students. Source of data in this research is primary and secondary data source. Primary data taken directly from the respondents and secondary data taken from documentary data MI Quraniah 8 Palembang, principals, administrative staff, teachers of study. The required data as mentioned above are obtained by oral and written test, observation, and documentation. Further analyzed by using statistical test with product moment formula and TSR (high, medium, low) to analyze the relationship of two variables. From the data analysis, it is found that the ability of reading Al-Qur'an of class V students in MI Quraniah 8 Palembang is categorized as medium, it is seen from 26 respondents there are 4 children who have high score (15,38%), 18 children in medium range (69,24%) and about 4 children is in low range (15,38%). While the skills to write Arabic letters class V students in MI Quraniah 8 Palembang also categorized as medium. From 26 respondents, thereare 4 children who have high scores (15,384%), while 16 children are in medium (61,539%) and the rest is about 6 children are in low range (23,077%). The final result of the research stated that there is a significant correlation between the two variables which the value of